Implementasi dan Pengaruh Time Division Multiplexing (TDM) terhadap Kualitas Transmisi Sinyal - Savira Rosa Ghozali; Andrijani Sumarahinsih (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
Time Division Multiplexing (TDM) is a multiplexing technique that enables the transmission of multiple signals over a single communication channel by allocating separate time slots for each signal stream. This study aims to analyze the working principles of TDM, examples of its implementation, as well as the benefits and drawbacks of TDM in communication networks. The findings show that TDM can enhance data transmission efficiency through flexible bandwidth allocation, minimizing signal interference and thereby improving signal quality. Due to these advantages, TDM is widely used in fiber optic communication systems, such as telephone and internet networks. Additionally, all data processing is conducted within integrated circuits utilizing Plastic Optical Fiber (POF), allowing TDM to be implemented at a low cost.